Mobile cognitive behavioral therapy for posttraumatic stress: Diving back in after hematopoietic stem cell transplant. Issue 10 (9th September 2022) - Mitchell, Hannah‐Rose; Smith, Sophia K.; Gebert, Rebecca; Applebaum, Allison J.
Key points: Cancer and Hematopoietic Stem Cell Transplant (HSCT) can be traumatic, especially when involving a life‐threatening incident (e.g., pulmonary embolism), but survivors often lack access to evidence‐based treatment due to cost, distance, and their immunocompromised status An HSCT survivor reported posttraumatic stress disorder (PTSD) symptoms precipitated by cancer and HSCT. Specifically, cancer‐specific triggers, like hearing or seeing the word "cancer, " and physical symptoms reminding her of the trauma were highly distressing The current case engaged in a stepped‐care intervention to manage PTSD symptoms: Four weeks of mobile health (mHealth) app use was followed by eight sessions of mHealth Cognitive Behavioral Therapy (mCBT) Tailored mCBT was successfully delivered remotely and showed promise in reducing cancer/HSCT‐specific PTSD symptoms In addition to reductions in PTSD symptoms, the current case demonstrated resilience and growth while participating in mCBT